2017
DOI: 10.1007/s10209-016-0521-9
|View full text |Cite
|
Sign up to set email alerts
|

Interactive testbed for research in autism—the SARA project

Abstract: The project Stylized Animations for Research on Autism (SARA) aims to develop a better understanding of the cognitive processes behind emotional categorization in children and adolescents with high-functioning autism spectrum disorder (ASD), in comparison with neurotypically developed peers. To this end, we combine novel realtime non-photorealistic rendering (NPR) algorithms, emotional facial animations, and eye-tracking technologies in a framework that serves as an interactive testbed for empirical research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Additionally, all studies matched ASD and NT groups on at least some characteristics, most commonly gender and age. The lowest scoring study on the quality appraisal was Arellano et al [ 36 ], due to a lack of information on how participants were recruited, and how ASD diagnoses were defined or confirmed. The highest scoring study on the quality appraisal was Berthoz et al [ 35 ], primarily due to their consideration of confounding factors in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, all studies matched ASD and NT groups on at least some characteristics, most commonly gender and age. The lowest scoring study on the quality appraisal was Arellano et al [ 36 ], due to a lack of information on how participants were recruited, and how ASD diagnoses were defined or confirmed. The highest scoring study on the quality appraisal was Berthoz et al [ 35 ], primarily due to their consideration of confounding factors in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, this was a version of the Bermond-Vorst Alexithymia Questionnaire. Two studies found a correlation between the BVAQ and TAS total scores [ 35 , 36 ], whilst the third study did not report this information [ 3 ]. Further information on study quality appraisals may be found in the appendix.…”
Section: Resultsmentioning
confidence: 99%
“…In two of these studies, the TAS-20 found significantly higher scores among autistic compared to typical populations, while the Bermond–Vorst Alexithymia Questionnaire (BVAQ) found no difference ( Berthoz & Hill, 2005 ; Silani et al, 2008 ). Similarly, Arellano and colleagues (2018) found TAS-26 scores were significantly higher in autistic populations, but no differences emerged in BVAQ scores. Findings from Erbas and colleagues (2013) are explored in the ‘Behavioural measures’ section.…”
Section: Resultsmentioning
confidence: 82%
“…Of the remaining 41 papers, 32 found significantly poorer emotional self-awareness in autism at α = 0.05. Of the remaining nine papers, two papers only examined TAS-20 subscales and four papers found mixed results with multiple tools ( Arellano et al, 2018 ; Berthoz & Hill, 2005 ; Erbas et al, 2013 ; Silani et al, 2008 ). In two of these studies, the TAS-20 found significantly higher scores among autistic compared to typical populations, while the Bermond–Vorst Alexithymia Questionnaire (BVAQ) found no difference ( Berthoz & Hill, 2005 ; Silani et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation